2000
DOI: 10.1097/00007632-200006010-00016
|View full text |Cite
|
Sign up to set email alerts
|

Lumbar Spinal Stenosis: Conservative or Surgical Management?

Abstract: The outcome was most favorable for surgical treatment. However, an initial conservative approach seems advisable for many patients because those with an unsatisfactory result can be treated surgically later with a good outcome.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

11
440
4
18

Year Published

2003
2003
2022
2022

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 623 publications
(473 citation statements)
references
References 45 publications
11
440
4
18
Order By: Relevance
“…Increasingly long-term outcomes are being expected of many clinical trials in back pain and spinal surgery as well as for clinical cohorts; however, this study adds credence to previous work on the outcome of decompression surgery which suggests that many of the key outcome namely function and pain demonstrate an initial dramatic reduction in the first 6-12 weeks followed by a plateaux in these outcomes [1,2], thus questioning the need for follow up beyond 1 year which can be costly and time consuming. This paper is important as it strengthens this argument particularly due to the low loss to follow up at 1 year, less than 5%, which is impressive and the authors should be commended on this and perhaps offer some advice to others on how to achieve such high rates of return.…”
supporting
confidence: 53%
“…Increasingly long-term outcomes are being expected of many clinical trials in back pain and spinal surgery as well as for clinical cohorts; however, this study adds credence to previous work on the outcome of decompression surgery which suggests that many of the key outcome namely function and pain demonstrate an initial dramatic reduction in the first 6-12 weeks followed by a plateaux in these outcomes [1,2], thus questioning the need for follow up beyond 1 year which can be costly and time consuming. This paper is important as it strengthens this argument particularly due to the low loss to follow up at 1 year, less than 5%, which is impressive and the authors should be commended on this and perhaps offer some advice to others on how to achieve such high rates of return.…”
supporting
confidence: 53%
“…Although reduced walking distance is an important component of the symptom complex of lumbar stenosis, the assessment of walking distance is relatively insensitive to change. Studies comparing surgery with conservative treatment for lumbar stenosis also found no differences between treatment groups regarding walking distance, although other outcome measures differed significantly between treatment groups [56,57].…”
Section: Discussionmentioning
confidence: 97%
“…The most commonly used therapy is a decompressive surgery. The success of this therapy reported in the literature varies from moderate to excellent results, depending on the point of interest for example pain reduction or neurological deficit [1,10,12]. One of the problems associated with decompression surgery is the creation of an instability as a consequence of the degeneration of the disc, the facetectomy or a combination of both [3].…”
Section: Introductionmentioning
confidence: 99%